Star Teacher Training- Manajemen kelas asyik menyenangkan - Sormin, Ayunda Sabrina; Mulyani, Heni; Agustina, Fitri; Nursahara; Suryani, Fatma (CV. Alfa Pustaka, 2025)
This training was provided to the teachers of SMA Negeri 1 Kota Padangsidimpuan, consisting of 20 teachers. The training took place in the SMA Negeri 1 Padamgsidimpuan Hall. The aim of this training was to address the common problem faced by most teachers, namely the difficulty in managing classrooms with diverse students. The Star Teacher training offered extensive classroom management practice through the BAM strategy (Belajar Asyik Menyenangkan). The focus of BAM is to provide teachers with theories and practical activities to help them understand student characteristics through five aspects: (1) Family Characteristics, (2) Personality, (3) Dominant Learning Style, (4) Ice Breaking, and (5) Cognitive Tests. The results of this training showed an improvement in teachers’ understanding of classroom management in dealing with diverse students through the practical stages of the BAM strategy. With this understanding, teachers will continue to be trained to become Star Teacher, beloved by their students so that the learning process becomes something students look forward to.